Revision of the Nepalese genus Microplinthus Zherichin, 1987 (Coleoptera: Curculionidae: Molytinae), with description of 25 new species - Meregalli, Massimo (Zootaxa, 2020)
The Nepalese genus Microplinthus Zherichin, 1987 is revised. The following 25 new species are described (type locality in parentheses): M. annapurnae (Annapurna Himal, Rambrong Danda, 28°23’N 84°13’E), M. arunensis (Khandbari Distr., forest S. Mansimgma, 27°30’N 87°20’E), M. brevipennis (Manaslu Himal, Bhara Pokhari, 28°18’N 84°28’E), M. durga (W Pokhara, near Ghorepani, 28°24’N 83°42’E), M. franzi (Kaligandakhi valley, between Lethe and Tukuche, 28°36’N 83°38’E), M. ganesha (Ganesh Himal, Rupchet, 28°05’N 85°09’E), M. godawaricus (Kathmandu, Phulchowki, 27°34’N 85°24’E), M. gupta (Helambu Himal, upper Chipling, 27°53’N 85°28’E), M. helambuensis (Central Nepal, between Mulkharka and Thare Pati, 28°08’N 85°22’E–28°02’N 85°29’E), M. jaegeri (W Pokhara, Mt. Panchase, 28°13’N 83°48’E), M. karnalicus (Karnali Distr. 5 km E Charta, 29°18’N 82°20’E), M. kaskianus (Kaski Distr., above Pothana, 28°19’N 83°51’E), M. kaumarya (Karnali Distr., Gotichaur valley, 29°12’10”N 82°18’56”E), M. khandbariensis (Khandbari Distr., above Seduwa, 27°34’N 87°15’E), M. koshianus (Koshi Prov., SW Chichilla, 27°27.01’N 87°13.13’E), M. letheensis (Kaligandakhi valley, between Lethe and Tukuche, 28°36’N 83°38’E), M. longipennis (Manaslu Himal, Bhara Pokhari lekh, 28°18’24”N 84°28’06”E), M. messneri (Panchtar Distr., Dhorpar Kharka, 27°05’N 87°55’E), M. newarorum (Phulchowki Distr., Lalitpur, 27°34’N 85°24’E), M. phulchowkianus (Kathmandu, Phulchowki, 27°34’N 85°24’E), M. rugosus (Solokhumbu Distr., Lamiura Danda, 27°34’N 86° 30’E), M. schmidti (Manaslu Himal, Dudh Pokhari lekh, 28°20’N 84°35’E), M. sherpa (Khandbari Distr., Bakan, 27°38’N 87°12’E), M. tamanus (Rolwaling Himal, upper Simigau, 27°51’N 86°15’E), M. yeti (Hinku Distr., Drangka Khola bridge, 27°35’N 86°47’E). A key for the identification of all species of Microplinthus is given. A phylogenetic analysis based on morphological characters of the species referable to the genera Falsanchonus, Microniphades and Microplinthus was carried out, implementing Bayesian Inference and Maximum Parsimony. Results indicate that the genera Falsanchonus and Microniphades are paraphyletic and are here treated as junior synonyms of Microplinthus.